Relasi Agama dan Politik Menurut Rawls - Ma'arif, Samsul (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2006)
The sections fall into some sections. The first one isintroduction to Rawls theoretical issues on politics especially onwhat is called PR. The misconceptions of Rawls thought held bysome religious believers will be dealt with explicitly. I will, then,try to explain that Rawls reflective equilibrium leaves room fordistinctively religious beliefs based on faith and religions. And, theoverlapping consensus which is crucial Rawls later thought. Based on this explanation above I come to second sectionthat deals with Indonesia’s political issues that is related toPancasila as a common ground. The issue is mainly on therelationship between religion and state in a highly diversitybackground especially diversity in religions. This section isremarkably important to see various ideologies took dialecticalprocess in its historical footprints. And, I come to third section. In this way, I will produce thepossibility of Pancasila as PR. Some frequent critical questionsresponding PR from the opposing groups will also be answeredclearly. In the final section, then, I try to give the explanation onreligion, as a comprehensive doctrine, should play a role inpolitical arena that in the light of Rawls’ PR.